Preparation method of transparent electrode film, transparent electrode film and application of transparent electrode film
By preparing transparent crystal thin layers on the substrate surface and forming conductive fibers, the existing transparent conductive electrodes have been solved, and a transparent electrode film with high light transmittance and low resistivity is realized, which improves the photoelectric conversion efficiency and reduces the preparation cost.
Patent Information
- Application Number
- CN202411746990.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing transparent conductive electrodes have insufficient light transmittance in ultraviolet and deep ultraviolet short-wave areas, resulting in limited photoelectric conversion efficiency, high production cost and complex process, making it difficult to achieve large-scale commercialization.
By preparing a transparent crystal thin layer on the surface of the substrate, periodically arranging the metal thin layer on its surface, applying a voltage to form a thin linear conductive channel, and then forming conductive fibers through annealing treatment, finally removing the residual metal thin layer to form a transparent electrode film.
It realizes a transparent electrode film with high light transmittance in ultraviolet and deep ultraviolet short-wave regions, which reduces resistivity and improves photoelectric conversion efficiency. It has a simple structure, low cost and is easy to prepare and produce applications on a large scale.
Smart Images

Figure CN119560232A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of conductive films, and in particular to a method for preparing a transparent electrode film, the transparent electrode film and applications thereof. Background Art
[0002] Transparent conductive electrodes, as unique materials that combine excellent conductive properties with excellent optical transparency, not only provide a solid foundation for the leap forward of modern electronic devices, but are also the core driving force for continuous innovation and development in the field of optoelectronic devices. Its application scope is widely penetrated into cutting-edge technology products such as solar cells, organic light-emitting diodes (OLEDs), liquid crystal displays (LCDs), touch screens, transparent heating devices, and smart windows, playing an indispensable core role. With the vigorous rise of emerging fields such as flexible display technology and wearable devices, the future application prospects of transparent conductive electrodes are becoming more and more broad, indicating that they will play a vital role in more high-tech fields.
[0003] However, there are still a series of challenges and difficulties in the research of transparent conductive electrodes. Figure 3 and Figure 4 As shown in the figure, although the traditional GaN and ITO surface electrode extension layers have low resistivity, they have strong absorption in short-wave regions such as ultraviolet and deep ultraviolet, and insufficient light transmittance, which seriously restricts the improvement of photoelectric conversion efficiency. In contrast, the transmittance of AlxG1-xN materials in the ultraviolet band increases significantly with the increase of Al component, but is accompanied by a sharp increase in resistivity, which has an adverse effect on the uniform distribution of current. Therefore, for materials such as AlGaN that have both high ultraviolet transmittance and high resistivity, exploring effective modification strategies to reduce their resistivity is of great significance for accelerating the research and development of ultraviolet optoelectronic devices and broadening their application scope.
[0004] At present, the research on transparent conductive electrodes is entering a new era of diversification and rapid development. Among them, metal nanofibers, especially silver nanowires (AgNWs) and copper nanowires (CuNWs), show great application potential in the field of flexible transparent conductive electrodes due to their excellent conductivity and light transmittance. Researchers continue to promote the leap in the performance of metal nanofiber transparent conductive electrodes by continuously optimizing the size, aspect ratio and arrangement structure of nanowires and innovating the preparation process. In addition, through advanced technologies such as chemical doping, composite material construction, and surface modification, researchers are committed to comprehensively improving the conductivity, light transmittance and mechanical strength of transparent conductive electrodes, and actively exploring low-cost, large-area production processes to achieve large-scale applications. In addition, researchers are also committed to improving the conductivity, light transmittance and mechanical properties of transparent conductive electrodes through doping, composite, surface modification and other methods, and exploring low-cost, large-area preparation processes to achieve large-scale production.
[0005] Despite this, the research on transparent conductive electrodes still faces many challenges, especially in the ultraviolet and deep ultraviolet short-wave regions. The preparation cost of new materials is high and the process is complex, making it difficult to achieve large-scale commercialization; the stability and durability of some materials need to be further improved to meet the requirements of long-term use; at the same time, they also face major challenges in flexible design, environmental protection and sustainability. Therefore, continued in-depth research and exploration in order to achieve breakthrough progress in AlGaN material modification and combining the characteristics of metal nanofibers to reduce resistivity is crucial to promoting the rapid development of the field of ultraviolet optoelectronic devices. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a transparent electrode film, a transparent electrode film and its application, which aims to overcome the above-mentioned problems existing in the prior art, and has both high conductivity and high transparency, simple structure, low cost and easy large-scale preparation and production application. As a key part of an optoelectronic device, it can improve the photoelectric conversion efficiency of the device and can be applied to many fields such as flexible electronics and transparent intelligent devices.
[0007] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a transparent electrode film comprises the following steps: Step (1), preparing a transparent crystal thin layer on the surface of the substrate; Step (2), preparing a plurality of metal thin layers arranged at intervals on the surface of the transparent crystal thin layer; Step (3), applying voltage to two adjacent metal thin layers, so that the transparent crystal thin layer between the two adjacent metal thin layers breaks down, forming a plurality of thin line-shaped conductive channels; Step (4), performing annealing treatment to diffuse metal atoms in the metal thin layer into the thin wire-shaped conductive channel to form conductive fibers; Step (5), removing the remaining metal thin layer to form a transparent electrode film.
[0008] Furthermore, the substrate is an ultraviolet LED epitaxial wafer, a detector epitaxial wafer or a solar cell epitaxial wafer.
[0009] Furthermore, the transparent crystal thin layer is one of AlN, GaN, AlxGa(1-x)N, Al2O3, and its doping type is undoped, n-type doped or p-type doped; the metal thin layer is one of Au, Ag, Ti, Cu, Cr, Ru, Ta, Pt, Pd, and Al.
[0010] Furthermore, the thickness of the transparent crystal thin layer ranges from [10nm, 100nm].
[0011] Furthermore, the thickness of the transparent crystal thin layer is 500 nm.
[0012] Furthermore, the thickness of the metal thin layer ranges from (0 to 40 nm], the width ranges from (0 nm to 300 nm], and the spacing between two adjacent metal thin layers ranges from (0 nm to 500 nm].
[0013] Furthermore, the thickness of the metal thin layer is 30 nm, the width is 200 nm, and the distance between two adjacent metal thin layers is in the range of 300 nm.
[0014] Furthermore, in the step (2), a plurality of spaced-apart graphic windows are first formed on the transparent crystal thin layer by a method selected from the group consisting of nanoimprinting, mask lithography, laser direct writing, and electron beam lithography; and then, the metal thin layer is prepared in each graphic window by a method selected from the group consisting of electron beam evaporation and magnetron sputtering.
[0015] Furthermore, in step (5), the remaining metal thin layer is removed by one of mechanical polishing, chemical polishing and etching.
[0016] The present invention also discloses a transparent conductive film obtained by any of the preparation methods described above, comprising a transparent crystal thin layer, the interior of the transparent crystal thin layer has a plurality of fine linear conductive channels formed by electrical breakdown, and metal atoms diffuse and fill the interior of the fine linear conductive channels to form conductive fibers.
[0017] The present invention also discloses an application of protecting a transparent conductive film having a structure as described above, wherein the transparent conductive film is prepared on an ultraviolet LED epitaxial wafer and is used as the positive electrode of the ultraviolet LED.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares a transparent crystal thin layer on the surface of a substrate, and prepares a periodically arranged metal thin layer on the transparent crystal thin layer. By applying a voltage between two adjacent metal thin layers, the transparent crystal metal thin layer between the metal thin layers is broken down to form a thin wire-shaped conductive channel; then, by annealing treatment, the metal atoms in the metal thin layer are diffused into the filament-shaped conductive channel to form a conductive fiber; finally, the metal thin layer arranged above the transparent crystal thin layer is removed to form a transparent electrode film. The transparent electrode film of the present invention has both high conductivity and high transparency, a simple structure, low cost, and is easy to prepare and produce on a large scale. In particular, it has high transmittance in the ultraviolet and deep ultraviolet short-wave regions, and is used as a conductive positive electrode of an ultraviolet LED, which can greatly improve the transmittance of the ultraviolet LED in the ultraviolet and deep ultraviolet short-wave regions. As a key part of an optoelectronic device, it can improve the photoelectric conversion efficiency of the device, and can also be applied to many fields such as flexible electronics and transparent intelligent devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of the layer structure of the substrate and the multi-level transparent conductive film before annealing treatment in the present invention.
[0020] Figure 2 It is a schematic diagram of the layer structure of the substrate and the multi-level transparent conductive film after annealing treatment in the present invention.
[0021] Figure 3 It is a schematic diagram of the structure of the substrate and the transparent conductive film in the present invention.
[0022] Figure 4 is the transmittance of different materials. Figure 5 is the resistivity of different compound materials. DETAILED DESCRIPTION
[0023] The specific implementation of the present invention is described below with reference to the accompanying drawings. In order to fully understand the present invention, many details are described below, but for those skilled in the art, the present invention can be implemented without these details.
[0024] like Figures 1 to 3 As shown, a method for preparing a transparent electrode film comprises the following steps: Step (1), preparing a transparent crystal thin layer 1 on the surface of substrate a.
[0025] Specifically, the transparent crystal thin layer 1 is prepared by a method selected from metal organic chemical vapor deposition, atomic layer deposition, physical vapor deposition, magnetron sputtering, and electron beam evaporation.
[0026] Wherein, the substrate a can be an ultraviolet LED epitaxial wafer, a detector epitaxial wafer or a solar cell epitaxial wafer. The thickness of the transparent crystal thin layer 1 ranges from [10nm to 100nm]; the preferred thickness is 50nm. The transparent crystal thin layer 1 is AlN, GaN, Al x Ga (1-x) N, one of Al2O3, and its doping type is non-doped, n-type doped or p-type doped; Al x Ga (1-x) N is, but is not limited to, Al 0.2 Ga 0.8 N.
[0027] Step (2), a plurality of metal thin layers 2 arranged in an interval are prepared on the surface of the transparent crystal thin layer 1; Figure 1 shown.
[0028] Specifically, a plurality of windows spaced apart are first formed on the transparent crystal thin layer 1 by a method selected from the group consisting of nanoimprinting, mask lithography, laser direct writing, and electron beam lithography; then, a metal thin layer 2 is prepared in each window by a method selected from the group consisting of electron beam evaporation and magnetron sputtering.
[0029] Among them, the thickness of the metal thin layer 2 ranges from (0, 40nm], the width ranges from (0nm, 300nm], and the spacing between two adjacent metal thin layers 2 ranges from (0nm, 500nm]. Preferably, the thickness of the metal thin layer 2 is 30nm, the width is 200nm, and the spacing between two adjacent metal thin layers 2 ranges from 300nm.
[0030] The metal thin layer 2 can be one of Au, Ag, Ti, Cu, Cr, Ru, Ta, Pt, Pd, and Al.
[0031] Step (3), applying voltage to two adjacent metal thin layers 2, so that the transparent crystal thin layer 1 between the two adjacent metal thin layers 2 is broken down, forming a plurality of thin line-shaped conductive channels.
[0032] Specifically, the voltage range is (0,100V].
[0033] Step (4) annealing is performed to diffuse the metal atoms in the metal thin layer 2 into the thin wire-shaped conductive channel to form conductive fibers 3. Figure 2 shown.
[0034] Specifically, the annealing temperature is 250-800° C., and the annealing time is 30 min-3 h.
[0035] Step (5), removing the remaining metal thin layer 2, thereby forming a transparent electrode film on the substrate a. Figure 3 shown.
[0036] Specifically, the remaining metal thin layer 2 is removed by one of mechanical polishing, chemical polishing and etching.
[0037] By controlling the thickness of the transparent crystal thin layer, the thickness, scale, periodic arrangement of the metal structure, and parameters such as annealing temperature and time in the above steps (1) to (5), the conductivity characteristics of the transparent conductive electrode can be controlled.
[0038] In addition, the present invention also discloses a transparent conductive film obtained by the above-mentioned preparation method, including a transparent crystal thin layer 1, wherein the transparent crystal thin layer 1 has a plurality of thin linear conductive channels formed by electrical breakdown, and metal atoms diffuse and fill the inside of the thin linear conductive channels to form conductive fibers 3. The above-mentioned transparent conductive film includes but is not limited to being applied to ultraviolet LEDs, and the transparent conductive film is prepared on the surface of the ultraviolet LED epitaxial wafer and used as the positive electrode of the ultraviolet LED.
[0039] Embodiment 1 Step (a1), obtaining a clean ultraviolet LED epitaxial wafer by chemical cleaning (using acetone, ethanol, deionized water and ultrasonic cleaning).
[0040] Step (1b): using a physical vapor deposition (PVD) method, a non-doped AlN transparent crystal thin layer is prepared on the surface of the LED epitaxial wafer, and the thickness of the AlN transparent crystal thin layer is 50 nm.
[0041] Step (1c), a printing layer is arranged on the AlN transparent crystal thin layer by a nanoimprint method, and a plurality of spaced graphic windows are formed by the printing layer, and then, an Au thin layer is prepared in each graphic window by an electron beam evaporation deposition method, and the thickness of the Au thin layer is 30 nm, thereby forming a plurality of spaced Au thin layers, that is, forming an Au thin layer array. Wherein, the graphic window includes but is not limited to a square with a cross section of 200nm×200nm, a groove with a depth of 30nm, and a spacing between two adjacent graphic windows of 300nm. A plurality of graphic windows are spaced and arranged to form a graphic array. In other words, the Au thin layer is a prism with a thickness of 30nm, a cross section of a square with a cross section of 200nm×200nm, a spacing between two adjacent Au thin layers of 300nm, and a period of the Au thin layer array is 500nm.
[0042] Step (1d): applying a voltage of 50 V between two adjacent Au thin layers to break down the AlN transparent crystal thin layer between them, thereby forming a plurality of thin line-shaped conductive channels.
[0043] Step (1e), placing the UV LED epitaxial wafer in an annealing furnace for annealing at a temperature of 500°C for 1 hour, so that the Au atoms in the Au thin layer diffuse into the filament-like conductive channels to form conductive fibers.
[0044] Step (1f), placing the UV LED epitaxial wafer in aqua regia, completely removing the remaining Au thin layer and printed layer on the AlN transparent crystal thin layer, thereby forming a transparent conductive film as an electrode on the surface of the UV LED epitaxial wafer.
[0045] Embodiment 2 Step (2a), obtaining a clean solar cell epitaxial wafer by chemical cleaning (using acetone, ethanol, deionized water and ultrasonic cleaning).
[0046] Step (2b), 10 -4In a high vacuum environment of 1.5 pa, a radio frequency power supply is used to ionize high-purity argon gas into high-energy argon ions, which then bombard the surface of the high-purity Al2O3 target material, causing the target atoms to be sputtered out and deposited on the surface of the solar cell epitaxial wafer. During the experiment, the sputtering power was precisely controlled in the range of 70W to 300W, the argon gas flow rate in the range of 50cm³ / min to 200 cm³ / min, and the working gas pressure in the range of 0.5Pa to 3.5Pa to obtain a high-quality, high-performance Al2O3 transparent crystal thin layer. Finally, a 50nm thick Al2O3 transparent crystal thin layer was formed on the solar cell epitaxial wafer.
[0047] Step (2c), by electron beam exposure technology, a plurality of spaced pattern arrays are formed on the Al2O3 transparent crystal thin layer coated with photoresist, and a plurality of pattern windows are formed after development; then, an Ag thin layer is prepared in each pattern window by electron beam evaporation method, thereby forming a plurality of spaced Ag thin layers, and the thickness of the Ag thin layer is 30 nm, that is, forming an Ag thin layer array. Wherein, the pattern window includes but is not limited to a circular cross-section with a diameter of 300nm and a groove with a depth of 30nm, and a plurality of such grooves are spaced and arranged, and the spacing between two adjacent pattern windows is 250nm, forming a pattern array. In other words, the Ag thin layer is a cylinder with a thickness of 30nm and a diameter of 300nm, and the spacing between two adjacent Ag thin layers is 250nm, and one period of the Ag thin layer array is 550nm.
[0048] Step (2d): applying a voltage of 30 V between two adjacent Ag thin layers to break down the Al2O3 transparent crystal thin layer between them, thereby forming a number of thin line-shaped conductive channels.
[0049] Step (2e), placing the solar cell epitaxial wafer in an annealing furnace for annealing at a temperature of 400°C for 2 hours, so that the Ag atoms in the Ag thin layer diffuse into the filament-like conductive channels to form conductive fibers.
[0050] Step (2f): using a mechanical polishing method to completely remove the remaining Ag thin layer on the AlN transparent crystal thin layer, thereby forming a transparent conductive film as an electrode on the surface of the solar cell epitaxial wafer.
[0051] The above is only a specific implementation of the present invention, but the design concept of the present invention is not limited thereto. Any non-substantial changes to the present invention using this concept shall be deemed as an infringement of the protection scope of the present invention.
Claims
1. A method for preparing a transparent electrode film, characterized in that: The following steps are involved: Step (1), preparing a transparent crystal thin layer on the surface of the substrate; Step (2), preparing a plurality of metal thin layers arranged at intervals on the surface of the transparent crystal thin layer; Step (3), applying voltage to two adjacent metal thin layers, so that the transparent crystal thin layer between the two adjacent metal thin layers breaks down, forming a plurality of thin line-shaped conductive channels; Step (4), performing annealing treatment to diffuse metal atoms in the metal thin layer into the thin wire-shaped conductive channel to form conductive fibers; Step (5), removing the remaining metal thin layer to form a transparent electrode film.
2. The method for preparing a transparent electrode film according to claim 1, characterized in that: The substrate is an ultraviolet LED epitaxial wafer, a detector epitaxial wafer or a solar cell epitaxial wafer.
3. A method for preparing a transparent electrode film according to claim 1 or 2, characterized in that: The transparent crystal thin layer is AlN, GaN, Al x Ga (1-x) N, one of Al2O3, and its doping type is non-doped, n-type doped or p-type doped; the metal thin layer is one of Au, Ag, Ti, Cu, Cr, Ru, Ta, Pt, Pd, and Al.
4. The method for preparing a transparent electrode film according to claim 1, characterized in that: The thickness of the transparent crystal thin layer ranges from [10 nm to 100 nm]. The method for preparing a transparent electrode film according to claim 1 is characterized in that the thickness of the transparent crystal thin layer is 500 nm.
5. The method for preparing a transparent electrode film according to claim 1, characterized in that: The thickness of the metal thin layer ranges from (0 to 40 nm), the width ranges from (0 nm to 300 nm), and the spacing between two adjacent metal thin layers ranges from (0 nm to 500 nm).
6. The method for preparing a transparent electrode film according to claim 5, characterized in that: The thickness of the metal thin layer is 30 nm, the width is 200 nm, and the distance between two adjacent metal thin layers is in the range of 300 nm.
7. The method for preparing a transparent electrode film according to claim 3, characterized in that: In the step (2), a plurality of spaced-apart pattern windows are first formed on the transparent crystal thin layer by a method selected from the group consisting of nanoimprinting, mask lithography, laser direct writing, and electron beam lithography; and then the metal thin layer is prepared in each pattern window by a method selected from the group consisting of electron beam evaporation and magnetron sputtering.
8. The method for preparing a transparent electrode film according to claim 1, characterized in that: In the step (5), the remaining metal thin layer is removed by one of mechanical polishing, chemical polishing and etching.
9. A transparent conductive film obtained by the preparation method according to any one of claims 1 to 8, characterized in that: It comprises a transparent crystal thin layer, wherein the interior of the transparent crystal thin layer has a plurality of thin linear conductive channels formed by electrical breakdown, and metal atoms diffuse and fill the interior of the thin linear conductive channels to form conductive fibers.
10. An application of the transparent conductive film according to claim 9, characterized in that: The transparent conductive film is prepared on an ultraviolet LED epitaxial wafer and is used as the positive electrode of the ultraviolet LED.
Citation Information
Patent Citations
Transparent conducting electrode based on graphene and manufacture method and applications thereof
CN101859858A
Transparent conductive substrate and manufacturing method thereof, thin-film solar cell and manufacturing method thereof
CN102298986A
Transparent conductive film and electric device
CN104103343A
Manufacture method of flexible transparent conductive membrane, and flexible transparent conductive membrane
CN104851523A
MnO2 / H-TiO2 nano composite array electrode material applied to super capacitor and preparation method thereof
CN106887338A